Penggunaan TOGAF ADM Untuk Mengidentifikasi Ketidaksesuaian Pada Aplikasi Pencari Kerja - Muhammad Anwar Fauzi; Ema Utami; Tonny Hidayat (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
Â The identification of non-conformities aims to create harmony between business and information technology for current and future organizational needs. The successful implementation of identification is inseparable from an organization planning and designing the enterprise architecture. Planning and designing this requires a complete and easy-to-use methodology. In this research, a case study was carried out for information system strategic planning by applying the TOGAF ADM method with the help of the value chain model and other modeling tools in job seeker applications. The stages of the TOGAF ADM methodology are translated into enterprise architecture modeling, namely vision architecture, business architecture, information system architecture and technology architecture. The results of modeling with the TOGAF ADM methodology provide a basis for overcoming problems and are an effort to optimize a data input design and add validation to the input design which can help reduce the risk of unwanted data such as duplicate data, inappropriate data and so on.